1953
DOI: 10.1039/tf9534900079
|View full text |Cite
|
Sign up to set email alerts
|

The semiconductivity of organic substances. Part 1

Abstract: An examination has been made of the effect of temperature on the d.c. electrical conductivity of a number of crystalline organic powders. Many substances show a semiconductivity possessing a definite activation energy E. In the uncompressed state, the " activation energy " E is largely influenced by crystal contacts. Under compression, a lower value of E is obtained which is probably characteristic of the crystals themselves. It is suggested that the excited orbitals of the 7~ electrons in the isolated molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
1

Year Published

1954
1954
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(44 citation statements)
references
References 5 publications
4
39
0
1
Order By: Relevance
“…As was noted in [18], a well-determined linear structure of a DNA consisting of stacks of pyrimidine-purine bases resembles stacking in unidimensional aromatic crystals. Numerous discussions have been devoted to the problem of whether a DNA with its aromatic compounds in the shape of stacks of heterocyclic base pairs forms a profile of a potential energy along which a charged particle can be transferred over a large distance.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…As was noted in [18], a well-determined linear structure of a DNA consisting of stacks of pyrimidine-purine bases resembles stacking in unidimensional aromatic crystals. Numerous discussions have been devoted to the problem of whether a DNA with its aromatic compounds in the shape of stacks of heterocyclic base pairs forms a profile of a potential energy along which a charged particle can be transferred over a large distance.…”
Section: Introductionmentioning
confidence: 57%
“…The hypothesis that a DNA may have conducting properties was first put forward in [18] shortly after the DNA helical structure had been discovered by Watson and Crick. As was noted in [18], a well-determined linear structure of a DNA consisting of stacks of pyrimidine-purine bases resembles stacking in unidimensional aromatic crystals.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the UVabsorption spectra of the A-and B-forms are practically the same strongly suggests that the electronic excitations primarily originate from the electrons in the basal planes rather than those involved in p z -delocalization in the perpendicular direction. 23 The circular dichroic (CD) spectra of Na þ DNA À and Q þ DNA À complexes in solution and in a dry film were studied by Tanaka and Okahata. 13 The authors demonstrated that the replacement of Na þ ions with Q þ ions did not change the conformation of the DNA backbone, and consequently, the basic features of the CD spectra did not change (Figure 3).…”
Section: Optical Properties Of Dnamentioning
confidence: 99%
“…Indeed, many organic compounds had been shown to have semiconducting [1] as well as photoconductive [2] properties, thus stimulating the interest of the physics and chemistry communities [3].…”
Section: Introductionmentioning
confidence: 99%